The importance of qualification of the human resources in tourism: a study applied to travel agents in Portuga - Ribeiro, Lígia Maria Rocha Pinto (2020)
Tourism has established itself as one of the most important and fastest growing economic sectors in the world. The success of this economic activity depends heavily on qualified human resources. In the case of travel agencies and tourism, travel agents are the pillar of all the dynamics of this subsector. In the absence of many specific studies on these professionals and their levels of qualification and job satisfaction, this article aims to define a profile of the travel agent in Portugal, by dividing it into four elements: socio‑demographic, professional, economic and psychological and also to understand the influence of the level of qualification. A descriptive quantitative methodology with univariate and bivariate analysis was applied using primary data collection, based on the questionnaire survey of a significant number of travel agents operating in Portugal, representative of the national territorial density. The empirical results of this study allowed the general conclusion that the vast majority of travel agents have higher education qualifications with incidence in the area. Travel agents with more years of profession tend to earn better wages, although agents in higher age brackets show lower educational qualifications. However, it is not because travel agents have more education that they will get better pay; such as travel agents with a degree in tourism feel less satisfied with their profession, this correlates with inappropriate pay and high levels of stress.